1995
DOI: 10.1038/376246a0
|View full text |Cite
|
Sign up to set email alerts
|

Natural selection of hemi- and heterozygotes for G6PD deficiency in Africa by resistance to severe malaria

Abstract: Glucose-6-phosphate dehydrogenase (G6PD) deficiency, the most common enzymopathy of humans, affects over 400 million people. The geographical correlation of its distribution with the historical endemicity of malaria suggests that this disorder has risen in frequency through natural selection by malaria. However, attempts to confirm that G6PD deficiency is protective in case-control studies of malaria have yielded conflicting results. Hence, for this X-linked disorder, it is unclear whether both male hemizygote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
346
5
7

Year Published

1996
1996
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 521 publications
(365 citation statements)
references
References 22 publications
7
346
5
7
Order By: Relevance
“…The coincident worldwide distribution of malaria and mutated G6PD alleles made "The malaria/G6PD hypothesis" generally accepted [46]. Further evidence of protection against severe P falciparum malaria comes from both epidemiological studies [47] as well as from in vitro work [48,49]. PK deficiency along with G6PD deficiency, are the two most frequent enzyme disorders causing chronic hemolytic anemia worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…The coincident worldwide distribution of malaria and mutated G6PD alleles made "The malaria/G6PD hypothesis" generally accepted [46]. Further evidence of protection against severe P falciparum malaria comes from both epidemiological studies [47] as well as from in vitro work [48,49]. PK deficiency along with G6PD deficiency, are the two most frequent enzyme disorders causing chronic hemolytic anemia worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…28 A large case-control study revealed an association between G6PD A− and a significant reduction in the risk of severe malaria for both G6PD female heterozygotes and male hemizygotes. 10 Other results suggested that female heterozygotes, but not male hemizygotes were protected against high parasite densities in Nigerian children with acute malaria, 8 and more precisely, that only G6PD A−/B heterozygote females gained an advantage against morbidity rates and parasitemia. 29 Unfortunately, this finding could not be further corroborated in the same population, 9 and it was rather suggested that protection against malaria was not afforded by G6PD deficiency itself, but by a related phenomenon to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, the geographical overlap between the distribution of G6PD deficiency and the endemicity of malaria has suggested that G6PD deficient subjects might be protected against malaria, but field studies have yielded conflicting results. [8][9][10] Polymorphisms of components of the inflammatory response have been investigated more recently, and among them, polymorphisms in the promoter region of the TNF-␣ gene are the most widely studied. Results from different study sites have varied in their ability to demonstrate an impact on the clinical outcome of P. falciparum infection.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22] Likewise, a protective effect against malaria has been associated with ␣ and ␤ thalassemias [23][24][25] and glucose-6-phosphate dehydrogenase deficiencies. 26,27 Finally, population-based association studies have detected several proteins that may play an important role in parasite invasion and host response to malaria. Promotor polymorphisms in the tumor necrosis factor ␣ (TNF␣) gene have been associated with malaria susceptibility.…”
Section: Genetic Factors In Susceptibility To Malaria In Humansmentioning
confidence: 99%